Handbook of comparative and historical Indo-European linguistics. - Klein, Jared S.; Joseph, Brian D.; Fritz, Matthias; Wenthe, Mark, 1978- (Handbücher zur Sprach- und Kommunikationswissenschaft ;, 2018)
"This book presents the most comprehensive coverage of the field of Indo-European Linguistics in a century, focusing on the entire Indo-European family and treating each major branch and most minor languages. The collaborative work of 120 scholars from 22 countries, Handbook of Comparative and Historical Indo-European Linguistics combines the exhaustive coverage of an encyclopedia with the in-depth treatment of individual monographic studies"--